Nature-Based Art Learning: A Strategy to Develop Aesthetic Experience and Ecological Awareness in Children Aged 5–6 Year - Yuliarini, Seni; Pamungkas, Joko (Journal of Educational Sciences, 2025)
Early Childhood Education (ECE) plays a crucial role in fostering children’s holistic development, including aesthetic experience and ecological awareness. This study explores the role of nature-based art learning as a strategy to develop both aspects in children aged 5–6 years. Using a descriptive qualitative approach, the study involved 46 children and 4 teachers at Kelompok Bermain Alam Uswatun Khasanah, Sleman. Data were collected through observation, interviews, and documentation during art sessions involving ecoprint and jumputan techniques with natural materials. Instruments were validated through expert judgment, and data accuracy was ensured through triangulation. Analysis followed the Miles and Huberman model. The results revealed that direct interaction with natural materials such as leaves, flowers, seeds, and plants not only enhanced children’s visual expression and aesthetic appreciation but also fostered ecological awareness. A total of 38 out of 46 children could articulate the meaning behind their artwork, while 31 demonstrated ecological understanding through inquiry and responsible behavior toward nature. Teacher reflections emphasized that this approach was more contextual and meaningful than conventional methods. These findings support the integration of nature-based art into the ECE curriculum and recommend further teacher training and quantitative studies to broaden the insights.